Inquiry Approach to Learning Can Be Applied in Christian Education Classroom - Iskandar, Srini M; Purwoko, Paulus Sentot (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
Inquiry approach to learning is one of the result of the paradigm shifts in education which had started in the early 1980. In spite of the bebefits of the inquiry approach to learning, many teachers/educators who apply teacher-centered learning are reluctant to apply it in their classrooms. They prefer to teaching using the lecturing method instead. The inquiry approach to learning is more beneficial to students than the lecturing method. Formerly the inquiry approach was only applied in natural science classes, but later on and up to now. It has been used in social science classes as well. Religion in classified as a branch of social studies, thus the inquiry approach to learning can also be used in Christian Education clasess. Based on the argument in this articles, the writer aim to show that applying the inquiry approach to learning in the Christian education classroom will give benefits to students as their performences will be improved and most of all. They will change from passive disinterested learners to active self motivated and self directed learners. As a result, the students will have deeper understanding about anything to discussed.